Transdiaphragmatic pericardiectomy in dogs. (28th January 2017) - De Ridder, M.; Kitshoff, A.; Devriendt, N.; Or, M.; Rubio – Guzman, A.; de Rooster, H.
Abstract : In patients with recurrent pericardial effusions, pericardiectomy is indicated. The purpose of this study was to describe a transdiaphragmatic approach for subtotal pericardiectomy in dogs and to evaluate its feasibility. In total, 20 canine cadavers weighing less than 10 kg (group S) and 20 weighing more than 20 kg (group L) were used. Within each group, half underwent a subphrenic pericardiectomy via an intercostal approach and half via a transdiaphragmatic approach. For each approach and within each weight group, the percentage of resected pericardium was calculated and compared. Additionally, a case series of nine consecutive client‐owned dogs that underwent a transdiaphragmatic pericardiectomy for pericardial effusion was reported. Exposure of pericardium and associated phrenic nerves was excellent in cadavers and clinical patients. In group S, the percentage of resected pericardium was not significantly different between the two approaches. In group L, on the other hand, the percentage of resected pericardium was lower with the transdiaphragmatic approach compared with the intercostal approach (P=0.001). In the clinical patients, no intraoperative complications were encountered and no recurrence of pericardial effusion was seen. Subtotal pericardiectomy via a transdiaphragmatic approach is straightforward and a safe surgical procedure to obtain permanent pericardial drainage in small and large breed dogs.